2008
DOI: 10.1177/154405910808700104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Oral Squamous Cell Carcinoma: Implications for Therapy

Abstract: The development of oral squamous cell carcinoma (OSCC) is a multistep process requiring the accumulation of multiple genetic alterations, influenced by a patient's genetic predisposition as well as by environmental influences, including tobacco, alcohol, chronic inflammation, and viral infection. Tumorigenic genetic alterations consist of two major types: tumor suppressor genes, which promote tumor development when inactivated; and oncogenes, which promote tumor development when activated. Tumor suppressor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
378
0
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(399 citation statements)
references
References 252 publications
0
378
0
21
Order By: Relevance
“…As low socio-economical status is also associated with poor oral hygiene conditions, which is an acknowledged risk factor for oral cancer 30 , we adjusted the analysis for educational level, as a proxy variable, in a attempt to control this effect, despite the fact that residual confounding might persist. Genetic susceptibility is another important related condition to the studied tumors 31 , but was not considered in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…As low socio-economical status is also associated with poor oral hygiene conditions, which is an acknowledged risk factor for oral cancer 30 , we adjusted the analysis for educational level, as a proxy variable, in a attempt to control this effect, despite the fact that residual confounding might persist. Genetic susceptibility is another important related condition to the studied tumors 31 , but was not considered in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings that CXCL13 enhances p-c-Jun levels and that JNK activity is up-regulated in SCC14a cells implicate CXCL13 in constitutive activation of activator protein complex transcription factors and in the malignant phenotype in OSCC cells. Studies indicate that STAT-1 transcription factor is up-regulated in oral cancer and implicated in OSCC development and growth (2). Previously it has been shown that signal transducers and activators of transcription 3 activation in stromal/osteoblastic cells is required for induced expression of RANKL by gp130-utilizing cytokines or IL-1 but not 1,25-dihydroxyvitamin D3 or PTH (32).…”
Section: Discussionmentioning
confidence: 99%
“…Etiologic factors for OSCC includes both a genetic predisposition (1) and exposure to carcinogens such as tobacco, alcohol, chronic inflammation, and the human papilloma virus infection (2). Previously, interleukin (IL)-6 and IL-8 have been implicated as potential biomarkers for OSCC (3).…”
Section: Introductionmentioning
confidence: 99%
“…Syrjänen et al first proposed in 1983 that HPV might be involved in the development of some OSCCs based on morphological and immunohistochemical features indicative of HPV infection (Syrjanen et al, 1983). In recent years, HPV has been recognized as an independent risk factor for a subset of OSCC (Choi et al, 2008;Marur et al, 2010). More than 200 different human papillomavirus (HPVs) types have been characterized (Psyrri et al, 2008), and at least 40 types can infect human genital tract (Munoz et al, 2003), of which HPV16 and HPV18 as main high-risk types are more closely linked with malignant tumors.…”
Section: Introductionmentioning
confidence: 99%